Imbalanced phytoplankton C, N, P and its relationship with seawater nutrients in Xiamen Bay, China. (February 2023) - Lu, Xiaoqian; Yu, Weiwei; Chen, Bin; Ma, Zhiyuan; Chen, Guangcheng; Ge, Feiyang; An, Shenqun; Han, Wenxuan
Abstract: Anthropogenic activities dramatically alter biogeochemical cycling and stoichiometry of carbon (C), nitrogen (N), and phosphorus (P) within coastal marine ecosystems. Long-term nutrient input has led to significant deviation of the C, N and P stoichiometry of phytoplankton (C167 N28 P1 ) and surface seawater (C1299 N24 P1 ) from the Redfield ratio (C106 N16 P1 ), and overall P-limitation in Xiamen Bay. The bio-P in phytoplankton was spatially consistent with that of inorganic P in seawater; and the phytoplankton bio-C:N:P shifted towards the same trend as the seawater under prolonged nutrient stress, as one of the cascade effects of the imbalanced seawater elemental stoichiometry on the species composition and abundance, and in turn on bio-elemental stoichiometry, of phytoplankton community. It is suggested that the significant deviations in elemental stoichiometry of primary producers might impair their capacity of nutrient supply for organisms at higher trophic-levels of the food chains in the local coastal ecosystem and thus damage its health. Graphical abstract: Unlabelled Image Highlights: Phytoplankton C, N, P stoichiometry of coastal bay is first reported in China. Phytoplankton C167 N28 P1 and seawater C1299 N24 P1 were both higher than C106 N16 P1 . Phytoplankton P distribution was consistent with SRP in the P-limited sea area. Phytoplankton may be limited by P due to imbalanced C:N:P input to seawater.